The Influence of Motivation and Commitment on Educator Performance in the Luwu SDA Mission - Kalengkongan, Eirene Paula Christanti; Prapunoto, Susana; Wijono, Sutarto (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
The study looks at the work-related motivation and dedication of educators and education staff in the Seventh-day Adventist Church Organization (SDA Church) in the Luwu Tanah Toraja Mission Area as indicators of their performance. The Seventh-day Adventist Church Organization (SDA Church) in the Luwu Tana Toraja Mission Area employs educators and education professionals, and the study examines their work-related motivation and dedication as performance indicators. This study found that motivation and commitment significantly predict the performance of educators and education personnel; however, motivation shows a more dominant influence compared to work commitment. These results support the importance of motivation and commitment in improving performance, although they only account for 16.9% of the variance. Further research is recommended to investigate other variables that affect performance and to expand the scope of the study.